USG Guided Quadaratus Lumburoum Block and Low Dose Spinal Anesthesia in Abdominal Surgeries - Rayamajhi, Anuj Jung; Dhungel, Bidur Kumar; Paudel, Subash; Paudel, Prashanta (Journal of Nepal Health Research Council, 2021)
Background: The postoperative analgesic efficacy of trans-muscular quadratus lumborum block in abdominal surgeries is well established; however, its intraoperative safety and efficacy as an anesthetic is still being explored. This retrospective case review was conducted to investigate the efficacy and safety of combined quadaratus lumburoum block and low-dose subarachnoid block for anesthesia in complex abdominal operations.Methods: Perioperative data of 29 patients, who underwent abdominal operations during the period of June/2019 to October/2019 under the combined technique, was analyzed. The primary outcome was intra and postoperative pain scores with the conox as qnox and numeric rating scale respectively at different time points. The secondary outcomes were intraoperative sedation scores with conox as qcon and perioperative dosage of fentanyl, changes in mean arterial pressure and the incidence of adverse events.Results: The mean qnox scores at incision, viscera dissection, closure and before transport to the post anesthesia care unit were between 44.66 and 55.79. The mean numeric rating scale scores before bed on the operation day, at 8 am on the first postoperative day, before bed on the first postoperative day and at 8 am on the second postoperative day were between 3.41 and 3.86. The mean qcon scores during the operations were between 61.31 and 65.82 while it was 85.66 following the stoppage of all sedations. The mean total perioperative consumption of fentanyl was 38.7mcg. The proportion of patients having MAP changes of less than 20% from baseline was 85.72%. The incidence of peri-operative adverse events was low.Conclusions: For complex abdominal operations, a combination of ultrasound-guided QLB-TM and low dose spinal anesthesia achieves adequate analgesia and is a safe technique.Keywords: Conox; continuous transmuscular quadratus lumborum block; high risk patients; laparotomy; low dose spinal anesthesia